Optimalisasi Peran Lembaga Keuangan Syariah dalam Mendorong Pertumbuhan UMKM di Era Ekonomi Digital - Riska Khayuni; Yurti Walida (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Islamic economics emerged as an alternative system based on Islamic principles to overcome inequality and social injustice in the conventional economic system. This article aims to examine the role of Islamic economics in achieving social justice through four main pillars: digitization of Islamic finance, empowerment of Sharia-based MSMEs, strengthening Islamic microfinance institutions, and optimizing ZISWAF (zakat, infaq, sadaqah, and waqf). This study uses a qualitative method with a literature review approach using national and international journals published since 2021. The results of the study show that Islamic economics has great potential in building a fair, inclusive, and sustainable economic system if supported by technological innovation, integrative policies, and improving public literacy. This research emphasizes the need for synergy between the government, Islamic financial institutions, business actors, and the community to strengthen the role of the Islamic economy in national development. In addition, it is necessary to strengthen regulations and cross-sector collaboration so that the implementation of the Islamic economy can run optimally in various lines of life. With sustained support, Islamic economics is believed to be able to be a solution to complex modern economic challenges.